Application of the PEN-3 Model to Tobacco Initiation, Use, and Cessation Among American Indian and Alaska Native Adults. Issue 4 (July 2016) - Hiratsuka, Vanessa Y.; Trinidad, Susan B.; Avey, Jaedon P.; Robinson, Renee F.
American Indian (AI) and Alaska Native (AN) communities confront some of the highest rates of tobacco use and its sequelae. As part of a formative research project investigating stakeholder understandings, preferences, and needs surrounding the use of pharmacogenetics toward tobacco cessation treatment, we sought to characterize sociocultural issues related to tobacco use and cessation. We used the PEN-3 cultural model to frame the research question and analysis of stakeholder interviews with 20 AI/AN patients, 12 health care providers, and 9 tribal leaders. Our study found high knowledge levels of the negative health effects of tobacco use; however, most patient participants ascribed negative health effects only to regular, heavy tobacco use and not to light use, which is more common in the population. The majority of patient participants did not endorse use of tobacco cessation treatment despite evidence of efficacy among AI/AN adults. Health promotion messaging to target low–tobacco consuming AI/AN people is needed. Additionally, messaging to promote tobacco cessation treatment using successful AI/AN former tobacco users to improve community perception of tobacco cessation treatment is recommended.